Development Of Melayu Cultural Mathematics Comic Media (Komadayu) In Mathematics Subject For Third Grade Students At SDN Batang Kuis - Ananda, Chairunnisa; Sari, Suci Perwita (PGMI IAIN Lhokseumawe, 2025)
This study aims to design and develop a comic-based mathematics learning media that integrates Melayu culture (KOMADAYU) into plane geometry learning for third-grade students at SDN 104230 Batang Kuis. The ADDIE development model, which comprises the phases of analysis, design, development, implementation, and evaluation, is the methodology employed in the Research and Development (R&D) technique. Observations, interviews, expert validation surveys, and teacher and student trials were used to gather data. The research results indicate that the KOMADAYU media received excellent ratings from experts, categorized as